The Effect of Learning Facilities and Family Environment on Motivation to Learn of Prospective Elementary Teacher Education on Online Learning - Mulyani, Eva Astuti; Alpusari, Mahmud; Putra, Elpri Darta (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
This research purpose determines the effect of learning facilities and family environment on motivation to learn of prospective elementary teacher on online learning. The research method used is descriptive quantitative. The data used are primary data obtained directly from filling out a questionnaire by 180 prospective elementary teacher education from a public University, Riau province, Indonesia. The results showed that there was a positive and significant effect of learning facilities and family environment on motivation to learn of prospective elementary teacher in learning during Pandemic, with the results of testing with the F test that obtained an F value of 21.272 with a significance value of F of 0.000 or a sig F value of <0.05. The multiple regression test results show that the coefficient of determination (R2) is 0.440 or 44%.